2022
DOI: 10.3389/fneur.2022.823202
|View full text |Cite
|
Sign up to set email alerts
|

Leveraging Factors of Self-Efficacy and Motivation to Optimize Stroke Recovery

Abstract: The International Classification of Functioning, Disability and Health framework recognizes that an individual's functioning post-stroke reflects an interaction between their health condition and contextual factors encompassing personal and environmental factors. Personal factors significantly impact rehabilitation outcomes as they determine how an individual evaluates their situation and copes with their condition in daily life. A key personal factor is self-efficacy—an individual's belief in their capacity t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
41
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(42 citation statements)
references
References 137 publications
(156 reference statements)
1
41
0
Order By: Relevance
“…It is well documented that it has a crucial influence on the treatment progress. The individual sense of self-efficacy affects the motivation to perform the appropriate behaviors necessary to achieve the desired rehabilitation outcomes [36,37]. Adequate levels of motivation significantly impact enhancing psychological functioning, increasing self-confidence, and improving the abilities needed to cope with the consequences of a neurological deficit, which in turn promotes a good prognosis in the long term [38,39].…”
Section: Discussionmentioning
confidence: 99%
“…It is well documented that it has a crucial influence on the treatment progress. The individual sense of self-efficacy affects the motivation to perform the appropriate behaviors necessary to achieve the desired rehabilitation outcomes [36,37]. Adequate levels of motivation significantly impact enhancing psychological functioning, increasing self-confidence, and improving the abilities needed to cope with the consequences of a neurological deficit, which in turn promotes a good prognosis in the long term [38,39].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, aspects of intrinsic motivation including effort/importance attributed to the task can also be influenced by the motivational statements as supported by the trend for higher effort/importance ratings reported by the motivation plus feedback group ( Supplementary Figure 6 ). This effect may be critical for motor skills that require dynamic and delicate motor control such as playing a musical instrument, operating a medical tool, or recovering compromised motor control through neurorehabilitation, where learning can be improved through incorporation of motivational statements during training ( Gangwani et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, several studies 15,22,[37][38][39][40][41] demonstrated that participating in art activities helped with relaxation, self-esteem, inspiration, and distraction in a stressful rehabilitation environment, which could lead to less depression in stroke patients. Gangwani et al 42 identified factors affecting post-stroke recovery that self-esteem, and motivation could promote good rehabilitation outcomes. Alwledat, et al 38 studied the effects of two sessions per week, 1.5 hours per session, for two weeks of creative art therapy on depression, anxiety, and stress on 85 stroke patients, which demonstrated that art activities could significantly reduce depression, anxiety, and stress in these participants.…”
Section: Depressionmentioning
confidence: 99%